2013
DOI: 10.1242/jeb.094177
|View full text |Cite
|
Sign up to set email alerts
|

Ultra miniature force plate for measuring triaxial forces in the micro newton range

Abstract: Measuring the ground reaction forces of a single leg is indispensable to understanding the dynamics of legged locomotion. Because of the technical state of the art, investigations are limited to animals with a body mass above 1 g. Here we present the design, fabrication, calibration and performance of a novel ultra-miniature force platform at the micronewton level. The sensor was built using the stereolithography technology and is equipped with semiconductor strain gauges. We found a highly linear signal respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…We used a 3D CAD and simulation software to design the force plate and to calculate its properties by the finite element method. For production of the prototype, we used the stereolithography technology and applied semiconductor strain gages to it (Reinhardt and Blickhan, 2014). Forces as great as 10 μN can be resolved with this sensor and the natural frequencies are above 200 Hz for all directions (see Table 5).…”
Section: Methodsmentioning
confidence: 99%
“…We used a 3D CAD and simulation software to design the force plate and to calculate its properties by the finite element method. For production of the prototype, we used the stereolithography technology and applied semiconductor strain gages to it (Reinhardt and Blickhan, 2014). Forces as great as 10 μN can be resolved with this sensor and the natural frequencies are above 200 Hz for all directions (see Table 5).…”
Section: Methodsmentioning
confidence: 99%
“…The two most prominent preparations investigated with in vitro CMOS MEAs so far are acute retina preparations from mice (Menzler and Zeck, 2011 ; Fiscella et al, 2012 ; Maccione et al, 2014 ), rats (Eickenscheidt et al, 2012 ; Lloyd et al, 2014 ; Stutzki et al, 2014 ), rabbits (Zeck et al, 2011 ; Ballini et al, 2014 ; Fiscella et al, 2014 ), guinea pig (Velychko et al, 2014 ) and humans (Reinhardt and Blickhan, 2014 ); and cultured neuronal cells from snails (Eversmann et al, 2003a ), rats (Hafizovic et al, 2007 ; Heer et al, 2007 ; Gandolfo et al, 2010 ; Lambacher et al, 2010 ; Bakkum et al, 2013 ; Ballini et al, 2014 ) and chicken (Hafizovic et al, 2007 ). Additionally, data from acute slices of the cerebellum (Frey et al, 2009a ; Obien et al, 2014 ), cortex (Ferrea et al, 2012 ; Medrihan et al, 2014 ) and olfactory bulb (Johnson et al, 2013a ) have been shown.…”
Section: Mea Technologymentioning
confidence: 99%
“…Techniques such as force plates, strain gauges, piezo-resistive sensors, micro-machined sensors, calibrated micropillars, and cantilevers have been employed with animals ranging in size from a few 100s of microns to a few centimeters. [1][2][3][4][5][6][7] Force measurements have also been carried out at lower length scales of 10s of microns for instance using individual cells. To investigate the role of the mechanical/physical environment, one can change the stiffness and/or viscosity of the surrounding medium or the substratum using biocompatible hydrogels.…”
mentioning
confidence: 99%